PERLINDUNGAN HUKUM TERHADAP PEMBERI HIBAH TERKAIT SURAT HIBAH HAK ATAS TANAH DIBAWAH TANGAN YANG DIBUAT DENGAN ITIKAD TIDAK BAIK - Elsa Kristina; Sudirman; Mardi Chandra (PT. Hasba Edukasi Mandiri, 2026)
Grant is a gift made by a person to another party that is carried out when the grantor is still alive in which there is no element of contra achievement. Granting a grant using a letter under the hand is an agreement whose implementation is carried out without the presence of an authorised party. This is done by the community to avoid costs and is considered easier to complete the administration. In law, grants are irrevocable. However, there are exceptions so that the grant can be withdrawn, such as the implementation of the grant is not in accordance with the provisions or does not fulfil the elements as the grant is implemented according to the applicable laws and regulations. The problems that will be discussed in this research are the legal consequences and legal protection of underhand grant letters made based on bad faith. which will be proven through the theory used, namely the theory of legal consequences and the theory of legal protection. The method used in this research is juridical-normative, namely library legal research with primary, secondary, and tertiary legal sources. The research approach used is the legislative approach, case approach, analytical approach, conceptual approach and legal material collection techniques are carried out by identifying book literature, journals, and other sources of legal material. For legal material analysis techniques carried out by 1) grammatical interpretation, 2) systematic interpretation and legal construction methods. By analysing the data using qualitative.